2001
DOI: 10.1051/0004-6361:20011265
|View full text |Cite
|
Sign up to set email alerts
|

Deep spectroscopy of the low-metallicity blue compact dwarf galaxy SBS 0335-052

Abstract: Abstract. The results of deep long-slit spectroscopy of the extremely low-metallicity blue compact dwarf (BCD) galaxy SBS 0335-052 are presented. Down to intensity levels of 10 −3...−4 of Hβ, unprecedented for spectroscopy of extra-galactic giant H ii regions, we detect numerous weak permitted and forbidden nebular lines in the brightest part of the galaxy. With varying degrees of confidence, the detections include lines of high-ionization ions like Fe 4+ -Fe 6+ , implying very hard ionizing radiation. Two bro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 14 publications
(23 reference statements)
6
77
0
Order By: Relevance
“…While the latter is strongest at the location of SSC 1, the former is offset in the direction of SSCs 4 and 5. This feature has been noted before by Izotov et al (1997aIzotov et al ( , 2001b. This is consistent with the idea that the extended He ii k4686 emission is due mainly to the ionizing radiation from radiative shocks, in contrast to the [O iii] k5007 emission, which originates mainly from the ionizing radiation of main-sequence stars.…”
Section: The Decoupling Of the Very Hard And Moderate Ionizing Radiatsupporting
confidence: 91%
See 2 more Smart Citations
“…While the latter is strongest at the location of SSC 1, the former is offset in the direction of SSCs 4 and 5. This feature has been noted before by Izotov et al (1997aIzotov et al ( , 2001b. This is consistent with the idea that the extended He ii k4686 emission is due mainly to the ionizing radiation from radiative shocks, in contrast to the [O iii] k5007 emission, which originates mainly from the ionizing radiation of main-sequence stars.…”
Section: The Decoupling Of the Very Hard And Moderate Ionizing Radiatsupporting
confidence: 91%
“…Several high-ionization emission lines are seen in its spectrum. In addition to the [Fe v] k4227 emission line already discussed by Fricke et al (2001) and Izotov et al (2001b) . This discovery confirms and strengthens the finding by Izotov et al (2001b), who discovered [Fe vi]-[Fe vii] emission in SBS 0335À052E and concluded that ionizing radiation above $7 ryd must be intense in this galaxy.…”
Section: Mmt Observations and Data Reductionmentioning
confidence: 61%
See 1 more Smart Citation
“…It was discovered in the Second Byurakan Survey by Izotov et al (1990) who noted its particularly low oxygen abundance of ∼12 + log(O/H) = 7.3, confirmed by subsequent studies (Melnick et al 1992;Izotov et al 2001). SBS 0335−052 is the most metal-poor galaxy known with an SFR ∼ 1 M yr −1 , 20 times higher than in I Zw 18 (Fanelli et al 1988;Hunt et al 2005b).…”
Section: Introductionmentioning
confidence: 87%
“…Morphological analogs to I Zw 18 may also exist among compact high-SSFR galaxies at intermediate redshift (0.1 < ∼ z < ∼ 0.8), such as compact narrow emissionline galaxies (Koo et al 1994;Guzmán et al 1998), luminous compact blue galaxies (Guzmán et al 2003;Puech et al 2006) and green pea (GP) galaxies (Cardamone et al 2009;Amorín et al 2010;Izotov et al 2011). The rest-frame EWs of GPs can in some cases almost compete with those of nearby XBCDs (see e.g., Izotov et al 2001b;Papaderos et al 2006b). …”
Section: Zw 18 As Local Morphological Template For Rapidly Assemblimentioning
confidence: 99%